Classical Histories, Colonial Objects: The Specimen Table Across Time and Space - Freya Gowrley (Yale University, 2021)
This article seeks to contextualise the production, purchase, and display of specimen tables in the eighteenth and nineteenth centuries, considering their fragmentary forms as a material result of both British neoclassicism and imperialism. Made for an audience of (often British) travellers, collectors, and settler colonists across the British empire and Continental Europe, specimen tables were named after the variety of specimens from which they were made, from pieces of marble (both newly sourced and procured from ancient ruins and monuments) to semi-precious hardstones and inlaid “exotic” woods. Reconceptualising the specimen table as a site that collapsed time and space, the article reads these objects through their fragmentary surfaces to explore how their interconnected forms echo their multitudinous connections across the complex geographies and temporalities of the British experience of travel and empire during the eighteenth and nineteenth centuries.